2013
DOI: 10.1159/000355943
|View full text |Cite
|
Sign up to set email alerts
|

Protein Restriction after Weaning Modifies the Calcium Kinetics and Induces Cardiomyocyte Contractile Dysfunction in Rats

Abstract: Protein restriction (PR) is associated with cardiovascular diseases. The purpose of this study was to investigate the effects on single ventricular cardiomyocyte contractile function of a short-term PR after weaning. Male Fischer rats that were 28 days old were randomly divided into a control group (CG, n = 16) and a protein-restricted group (PRG, n = 16). After weaning, CG and PRG animals received isocaloric diets containing 15 and 6% protein, respectively, for 35 days. Biometric parameters were then measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…; Penitente et al . ). Another important finding here is that recovery did not fully revert resting tachycardia, suggesting that abnormalities in chronotropic control are more profound and may not be reinstated to normal.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Penitente et al . ). Another important finding here is that recovery did not fully revert resting tachycardia, suggesting that abnormalities in chronotropic control are more profound and may not be reinstated to normal.…”
Section: Discussionmentioning
confidence: 97%
“…; Penitente et al . ). Data in the literature have also shown that increased sympathetic drive to the cardiovascular system can be associated with both an increase in the action of the renin–angiotensin system on peripheral mechanisms controlling circulation and changes in central pathways controlling the autonomic system.…”
Section: Introductionmentioning
confidence: 97%
“…Several hypotheses have been suggested to explain the hemodynamic changes associated with malnutrition. Considering the model investigated, appears to be more relevant the hypothesis of reduced amino acids bioavailability, which is associated to structural abnormalities of the parenchyma and stroma in different organs of the cardiovascular system, especially the heart [2,9]. Furthermore, a lower efficiency in the synthesis of peptide regulatory molecules such as neurotransmitters, growth factors and intracellular signaling molecules can also directly associated with reduced amino acids levels [6].…”
Section: Discussionmentioning
confidence: 99%
“…The left ventricles (LV) were dissected and weighed separately [9]. The relative heart and LV weight was calculated by dividing the heart mass and LV mass by the tibia length (TL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation